2006
DOI: 10.1088/0960-1317/16/12/030
|View full text |Cite
|
Sign up to set email alerts
|

A compact, low-cost microliter-range liquid dispenser based on expandable microspheres

Abstract: This work presents a new low-cost liquid dispenser for the dispensing of microliters to milliliter volumes. The dispensing mechanism is based on a thermal actuator where highly expandable microspheres expand into a liquid reservoir consequently displacing any stored liquid. All device components are made out of low-cost materials and the fabrication process has the potential for high volume batch manufacturing. The device utilizes the property of the expandable microspheres to form a heat insulating layer betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Integrated with a simple liquid propulsion mechanism, a patch-like system can be designed where the seals break once the device is actuated. An example of such an actuator capable of generating pressures above 100 kPa was previously introduced by us (Roxhed et al 2006), and demonstrated in use with non-sealed microneedles for insulin delivery in vivo (Nordquist et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Integrated with a simple liquid propulsion mechanism, a patch-like system can be designed where the seals break once the device is actuated. An example of such an actuator capable of generating pressures above 100 kPa was previously introduced by us (Roxhed et al 2006), and demonstrated in use with non-sealed microneedles for insulin delivery in vivo (Nordquist et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The automotive industry use microspheres in underbody coatings, tires, composite materials, and for adhesive debonding 9–12. Interesting new applications of microspheres are as single‐use pumps or valves in microfluidic systems13, 14 or as sacrificial templates in the production of foamed ceramics 15, 16…”
Section: Introductionmentioning
confidence: 99%
“…8 The automotive industry use microspheres in underbody coatings, tires, composite materials, and for adhesive debonding. [9][10][11][12] Interesting new applications of microspheres are as singleuse pumps or valves in microfluidic systems 13,14 or as sacrificial templates in the production of foamed ceramics. 15,16 The expansion temperature, particle size, maximum expansion, and the microsphere surface chemistry are all important parameters when choosing the appropriate microsphere grade.…”
Section: Introductionmentioning
confidence: 99%
“…This transition is essentially irreversible. Once the sphere is cooled, it remains in its expanded state (Roxhed et al 2006;Griss et al 2002).…”
Section: Thermo-responsive Pdms Valvesmentioning
confidence: 99%